The book that changed Europe : Picart & Bernard's Religious ceremonies of the world - Hunt, Lynn, 1945-; Jacob, Margaret C., 1943-; Mijnhardt, W. W., 1950- (Belknap Press of Harvard University Press, 2010)
"Two French Protestant refugees in eighteenth-century Amsterdam gave the world an extraordinary work that intrigued and outraged readers across Europe. In this captivating account, Lynn Hunt, Margaret Jacob, and Wijnand Mijnhardt take us to the vibrant Dutch Republic and its flourishing book trade to explore the work that sowed the radical idea that religions could be considered on equal terms. Famed engraver Bernard Picart and author and publisher Jean Frederic Bernard produced The Religious Ceremonies and Customs of All the Peoples of the World, which appeared in the first of seven folio volumes in 1723. They put religion in comparative perspective, offering images and analysis of Jews, Catholics, Muslims, the peoples of the Orient and the Americas, Protestants, deists, freemasons, and assorted sects. Despite condemnation by the Catholic Church, the work was a resounding success. For the next century it was copied or adapted, but without the context of its original radicalism and its debt to clandestine literature, English deists, and the philosophy of Spinoza. Ceremonies and Customs prepared the ground for religious toleration amid seemingly unending religious conflict, and demonstrated the impact of the global on Western consciousness. In this beautifully illustrated book, Hunt, Jacob, and Mijnhardt cast new light on the profound insight found in one book as it shaped the development of a modern, secular understanding of religion."--Cover